The effects of China’s economic diplomacy on its relations with selected Central and East European countries - Čadilová, Karolína; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The thesis examines the impact of economic diplomacy on the relations between the People's Republic of China and Central and Eastern European (CEE) countries, with a specific focus on the 16+1 project. The main aim is to find out the impact of possible differences in China's economic diplomacy towards individual countries on the participation of those countries in the 16+1 cooperation framework and their relations with China. For this aim, the thesis sets out the following questions: How has the uneven use of economic diplomacy by China affected its relations with countries participating in the project? What other possible causes could have led to countries joining or leaving the 16+1 project? The methodology is exploratory in nature, presenting two case studies on Lithuania and Greece and their relations with China and subsequent comparative analysis of the two case studies. The thesis finds that the lack of actual investment and security concerns in Lithuania led the country to leave the 16+1 framework. In contrast, Greece's close relations with China were based on continuous Chinese investments, especially in the port of Piraeus, which among other factors, led Greece to join 16+1. The domestic political situation was found to be a leading secondary factor in both cases. Another factor was the EU's criticism of China and its stance on human rights issues. Overall, the thesis explains the complex relationships between economic diplomacy, security, human rights, and internal politics that influenced the development of the 16+1 project.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses